Dysphonia Outperforms Voice Change as a Clinical Predictor of Dysphagia - Griffin, Lindsay; Kamarunas, Erin; Smith, Julian Bergen; Kuo, Christina; O, 'Donoghue Cynthia (American Journal of Speech-Language Pathology, 2023)
Purpose: Changes in voice quality after consuming food or drink have been used as a clinical indicator of dysphagia during the clinical swallowing evaluation (CSE); however, there is conflicting evidence of its efficacy. This study investigated if dysphonia and/or voice change after swallowing are valid predictors of penetration, aspiration, or pharyngeal residue. Our approach aimed to improve current methodologies by collecting voice samples in the fluoroscopy suite, implementing rater training to improve interrater reliability and utilizing continuous measurement scales, allowing for regression analyses. Method: In this prospective study, 30 adults (aged 49–97 years) referred for a videofluoroscopic swallowing study (VFSS) were audio-recorded completing a sustained /i/ prior to VFSS and again after swallowing each bolus during the VFSS. Swallowing function was measured using the reorganized Penetration–Aspiration Scale and the Normalized Residue Ratio Scale. Following listener training, 84 voice samples were perceptually rated using the Consensus Auditory-Perceptual Evaluation of Voice (CAPE-V). Ordinal and logistic regression were used to determine whether voice quality and voice quality change after swallowing were predictors of airway invasion and pharyngeal clearance. Results: Results indicated that the presence of dysphonia at baseline during a sustained /i/ task as measured by the CAPE-V predicted airway invasion but not pharyngeal residue. Voice change after swallowing associated with vowel /i/ production as measured by the CAPE-V did not predict either dysphagia measure. Conclusion: These results indicate that voice change during a sustained /i/ after swallowing appears unrelated to airway invasion or pharyngeal residue; however, in the absence of known laryngeal pathology, dysphonia prior to a CSE should alert speech-language pathologists of a possible comorbid dysphagia.
0 citations (Crossref) [2023-10-31]
Keywords: dept.cmd; peer-reviewed